Major paradigm shifts in NRM in Australia. (6th December 2007) - Robins, Lisa
This paper examines the influence of global discourses on policies and programmes for Natural Resource Management (NRM) in Australia, and the emergence of 56 formalised regional NRM bodies and their community-based Boards of management with responsibilities for NRM planning and implementation. It traces the emergence of the 'landcare movement' and the trend toward 'Integrated Catchment Management (ICM)', including governments around Australia embracing greater community input. It examines 'sustainable development' and 'neoliberalism', which have been advocated in concert, but with signs of the latter dominating. The formalisation of 'regionalism' for NRM in Australia has marked a shift in power and resources from the state level to both the federal and regional levels. What remains to be seen is whether the responsibilities devolved to regional NRM bodies and their Boards are realistically within their capacities to deliver.